Labile plasma iron and echocardiographic parameters are associated with cardiac events in β‐thalassemic patients. (27th January 2023) - Ferrara, Francesca; Coppi, Francesca; Riva, Roberta; Ventura, Paolo; Ricci, Andrea; Mattioli, Anna Vittoria; Talarico, Marisa; Garuti, Cinzia; Bevini, Mirco; Rochira, Vincenzo; Buzzetti, Elena; Pietrangelo, Antonello; et al.
Abstract: Background and Aim: Notwithstanding the improvement in therapies, patients affected by thalassemia major (TM) and intermedia (TI) are still at high risk of cardiac complications. This study aimed at evaluating the incidence and predictive factors for developing cardiac events in adult β ‐TM and TI patients. Population and Methods: Data on diagnosis and clinical history were collected retrospectively; prospective data on new‐onset cardiac failure and arrhythmias, echocardiographic parameters, biochemical variables including non‐transferrin‐bound iron (NTBI) and labile plasma iron (LPI), magnetic resonance imaging (MRI) T2* measurement of hepatic and cardiac iron deposits, and iron chelation therapy were recorded during a 6‐year follow‐up. Results: Thirty‐seven patients, 29 TM and 8 TI, were included. At baseline, 8 TM patients and 1 TI patient had previously experienced a cardiac event (mainly heart failure). All patients were on chelation therapy and only 3 TM patients had mild‐to‐severe cardiac siderosis. During follow‐up, 11 patients (29.7%) experienced a new cardiac event. The occurrence of cardiac events was correlated to high LPI levels (OR 12.0, 95% CI 1.56–92.3, p .017), low mean pre‐transfusion haemoglobin (OR 0.21, 95% C.I. 0.051–0.761, p .21) and echocardiographic parameters suggestive of myocardial hypertrophy. Multivariate analysis disclosed high LPI and left ventricle mass index (LVMI) as independent variables significantly associated with cardiac events. Cardiac iron deposits measured by MRI T2* failed to predict cardiac events. Conclusion: LPI, Hb levels and echocardiographic parameters assessing cardiac remodelling are associated with cardiac events in adult TM and TI patients. LPI might represent both a prognostic marker and a potential target for novel treatment strategies. Further studies are warranted to confirm our findings on larger populations.